Design and Implementation of a Global Health and Underserved Care Track in an Otolaryngology Residency - Matthew J. Urban MD; Ashok A. Jagasia MD, PhD; Pete S. Batra MD; Phillip LoSavio MD (OTO Open, 2022)
Despite widespread resident interest in global health and underserved care, few otolaryngology residency programs offer a formal global health experience. This article is the first to characterize a formal otolaryngology global health and underserved care track with a focus on how this curriculum integrates with and supplements resident education. Components of the track include longitudinal limited-resource field experiences in domestic and abroad settings, a related quality improvement project, and completion of a formalized global health educational curriculum. In addition to delivering humanitarian aid, residents in this track obtain a unique educational experience in all 6 core competencies of the Accreditation Council for Graduate Medical Education. Early barriers to implementation included identifying mentorship, securing funding, and managing busy resident schedules. In this work, we detail track components, schedule by track year, keys to implementation, and potential educational pitfalls.